Using slow frame rate imaging to extract fast receptive fields - Omer Mano (Nature Portfolio, 2019)
The temporal resolution of optical measurements of neural activity has traditionally been limited by the image or volume acquisition rate. Here, the authors describe an analysis that exploits the short duration of neural measurements within each image to extract neural responses at higher temporal resolution than the acquisition rate.